2012
DOI: 10.1136/bjsports-2012-091480
|View full text |Cite
|
Sign up to set email alerts
|

Sport concussion knowledge base, clinical practises and needs for continuing medical education: a survey of family physicians and cross-border comparison

Abstract: Existing published recommendations regarding diagnosis/management of concussion are not always translated into practise, particularly the recommendation for cognitive rest; predicating enhanced, innovative CME initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 51 publications
6
33
0
Order By: Relevance
“…Johnson et al's study concludes with the need for DCs to become more aware of current guidelines and assessment tools. 37 This study concurs with Lebrun et al 36 regarding the need for better dissemination and knowledge transfer of assessment tools and current guidelines to first-contact medical physicians. This pilot study found prospective professional differences in particular aspects of recognition of the TBI patient, but was statistically inconclusive, indicating a need for further study.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Johnson et al's study concludes with the need for DCs to become more aware of current guidelines and assessment tools. 37 This study concurs with Lebrun et al 36 regarding the need for better dissemination and knowledge transfer of assessment tools and current guidelines to first-contact medical physicians. This pilot study found prospective professional differences in particular aspects of recognition of the TBI patient, but was statistically inconclusive, indicating a need for further study.…”
Section: Discussionsupporting
confidence: 71%
“…36 Studies of medical students and neurology/neurosurgery residents revealed that 32% were either sure they never learned about concussions or could not remember if they had ever learned about concussions in their undergraduate medical education, 29 whereas other studies indicated that 63% of neurologists did not receive the MTBI education. 19 The Zurich guidelines acknowledge the need for more knowledge transfer, 21,38 and others report that it is critical for evidence-informed practices to implement new information and make the best clinical decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…42 Lebrun et al found that family physicians in Alberta and North Dakota rarely recommended cognitive rest (47.5% and 28%, respectively), despite existing guidelines. 43 Bazarian et al examined pediatric, family, and emergency providers in Rochester, New York, on their knowledge of concussion grading and similarly found that the correct application of return-to-play guidelines was below 57%. That study examined knowledge of the pre-2002 definition of concussion.…”
Section: Discussionmentioning
confidence: 99%